Study of spatial inhomogeneity in inverted all‐polymer solar cells: Effect of solvent and annealing. Issue 11 (16th March 2015) - Perulli, Andrea; Lattante, Sandro; Persano, Anna; Cola, Adriano; Di Giulio, Massimo; Anni, Marco
ABSTRACT: The efficiency optimization of bulk heterojunction solar cells requires the control of the local active materials arrangement in order to obtain the best compromise between efficient charge generation and charge collection. Here, we investigate the large scale (10–100 μm) inhomogeneity of the photoluminescence (PL) and the external quantum efficiency (EQE) in inverted all‐polymer solar cells (APSC) with regioregular poly(3‐hexylthiophene) (P3HT):poly(9, 9‐dioctylfluorene‐co‐benzothiadiazole) (F8BT) active blends. The morphology and the local active polymer mixing are changed by depositing the active layer from four different solvents and by thermal annealing. The simultaneous PL and EQE mapping allowed us to inspect the effects of local irregularities of active layer thickness, polymer mixing, polymer aggregation on the charge generation and collection efficiencies. In particular, we show that the increase of the solvent boiling point affects the EQE non‐uniformity due to thickness fluctuations, the density non‐uniformity of rrP3HT aggregate phase, and the blend components clustering. The thermal annealing leads to a general improvement of EQE and to an F8BT clustering in all the samples with locally decrease of the EQE. We estimate that the film uniformity optimization can lead to a total EQE improvement between 2.7 and 6.3 times. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2015, 53, 804–813 Abstract : Combined confocal photoluminescence and photocurrent microscopy are used to investigate the correlation between local radiative recombination and charge extraction of rrP3HT:F8BT inverted all‐polymer solar cells (APSC), with active layer deposited under different conditions (variation of the solvent and thermal annealing). A strong non‐uniformity of the charge generation and extraction is evidenced. The optimization of the power conversion efficiency of APSC requires the control of the local active materials arrangement.